2017
DOI: 10.1111/roie.12302
|View full text |Cite
|
Sign up to set email alerts
|

Good and useless FDI: The growth effects of greenfield investment and mergers and acquisitions

Abstract: We explore the effect of foreign direct investment (FDI) on economic growth, distinguishing between mergers and acquisitions (M&As) and "greenfield" investment. A simple model underlines that, unlike greenfield investment, M&As partly represent a rent accruing to previous owners, and do not necessarily contribute to expanding the host country's capital stock. Greenfield FDI should therefore have a stronger impact on growth than M&A sales. This hypothesis is supported by our empirical results that are based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
98
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(108 citation statements)
references
References 80 publications
8
98
0
2
Order By: Relevance
“…In this context, some scholars have focused on the FDI-growth nexus and discovered that FDI inflows made a positive contribution to the economic growth (e.g., see Borensztein et al, 1998;Li & Liu, 2005;Pegkas, 2015;Iamsiraroj & Ulubaşoğlu, 2015;Iamsiraroj, 2016). However, few scholars have investigated the interaction among greenfield and brownfield investments and economic growth and revealed different findings (e.g., see Calderon et al, 2004;Wang & Wong, 2009;Neto et al, 2010;Harms & Meon, 2014;Eren & Zhuang, 2015;Zvezdanović-Lobanova et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some scholars have focused on the FDI-growth nexus and discovered that FDI inflows made a positive contribution to the economic growth (e.g., see Borensztein et al, 1998;Li & Liu, 2005;Pegkas, 2015;Iamsiraroj & Ulubaşoğlu, 2015;Iamsiraroj, 2016). However, few scholars have investigated the interaction among greenfield and brownfield investments and economic growth and revealed different findings (e.g., see Calderon et al, 2004;Wang & Wong, 2009;Neto et al, 2010;Harms & Meon, 2014;Eren & Zhuang, 2015;Zvezdanović-Lobanova et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Harms and Meon (2014) analyzed the influence of greenfield and brownfield FDIs on the economic growth in 78 countries from emerging and developing economies over the period of 1987-2005 employing panel regression and revealed that greenfield FDIs positively influenced the economic growth, while brownfield FDIs made no significant contributions to economic growth. Eren and Zhuang (2015) researched the influence of greenfield and brownfield FDIs on economic growth in 12 EU members (10 Central and Eastern European states, Cyprus and Malta) over the period of 1999-2010 employing panel regression and discovered that both greenfield and brownfield FDIs did not make a significant contribution to the economic growth on their own, their impacts depend on the absorptive capacities of the countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 GF investment inflows finance the construction of new facilities which augment the stock of physical capital and thus expand the production capacity in countries, creating new jobs and increasing market competition (Mattoo et al 2004). M&As predominantly involve a change in ownership via the purchase of existing assets, although they might result in a more efficient allocation of resources (Kim 2009;Wang and Wong 2009;Harms and Méon 2012). 4 Importantly, whereas most global FDI waves have been associated with an increase in mergers and acquisitions (M&A) (Brakman et al 2006), the extent to which greenfield (GF) investments contribute to surges and stops in FDI in developing countries remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The literature originated with Calvo (1998) and broadened to include different conditions as well as the opposite events such as ''surges'', defined as sharp increases in net capital flows (Reinhart and Reinhart 3 However, both modes are associated with increases in aggregate productivity. 4 M&A sales create rents for the previous owners which are not necessarily channeled into new investments (Harms and Méon 2012). Yet, M&As might rely more on local and regional supplier networks than multinationals entering through greenfield investments (Wes and Lankes 2001).…”
Section: Introductionmentioning
confidence: 99%
“…12 The unconditional probability of experiencing a surge in greenfield FDI and M&As was 11.7% and 3.2%, respectively; the unconditional probability of experiencing a greenfield-led stop was 12.8%, compared to 3.3% for M&As. 13 According to Harms and Méon (2011), a larger share of M&A sales merely represents a rent that accrues to incumbent owners.…”
mentioning
confidence: 99%